Efficient photocatalytic activity of MnO2-loaded ZrO2/carbon cluster nanocomposite materials under visible light irradiation - Matsui, Hiroshi; Bandou, N.; Karuppuchamy, Subbian; Hassan, Mohd Ali; Yoshihara, Masakuni (Elsevier, 2012)
Nano-sized ZrO2/carbon cluster nanocomposite material was successfully prepared by the calcination of Zr(acac)4/epoxy resin complex in air. The composite material obtained by calcining at 200 °C was treated with hydrogen hexachloroplatinate hexahydrate (H2PtCl6) to obtain Pt-loaded materials denoted as Ic200Pt'sH's. The Pt-loaded material modified with MnO2 particles efficiently decompose water into H2 and O2 with a [H2]/[O2] ratio of 2 under the irradiation of visible light (λ > 460 nm) through the electron transfer process of MnO2 → carbon clusters → ZrO2 → Pt.